Analysis of total cholesterol levels in public infrastructure and facilities officers (petugas PSU) in Kelurahan Rawa Buaya Jakarta Barat - Cahyani, Meirani Dwi; Hikmah, Aulia Mutiara (Journal of Indonesian Medical Laboratory and Science, 2024)
Background: The basic need for food must be fulfilled by humans as a fulfillment of energy sources in carrying out activities. Consumption of fat macromolecules has the highest energy compared to other macromolecules. However, excessive consumption of fat can also increase cholesterol in the blood. Public Infrastructure and Facilities Officers (PPSU) do a lot of outdoor work so it is possible to have unhealthy eating habits such as frequently consuming fatty foods. Objectives: The purpose of this study was to determine qualitatively the distribution of total cholesterol levels in PPSU in Rawa Buaya Village. This research is descriptive-analytic. Materials and Methods: The research sample was obtained using a purposive sampling technique with inclusion and exclusion criteria involving 67 respondents. Results: The results showed that the majority of respondents were male, with 65 respondents (97%). From the results of the age group category, 24 people (35.8%) were dominated by respondents aged 31-40 years. Conclusions: The overall average cholesterol level of respondents is 201 mg/dL. If distributed by gender, female respondents have an average total cholesterol level of 237 mg/dl and men have an average total cholesterol level of 200 mg/dL.